EFFECTIVENESS OF SMARTPHONE-BASED SPIRITUAL NURSING CARE ON ANXIETY IN CHILDREN - Arbianingsih Arbianingsih; Huriati Huriati; Eka Hadrayani; Aswi Aswi (Poltekkes Kemenkes Gorontalo, 2026)
Background: Hospitalization is a significant stressor in children and is frequently associated with heightened anxiety. Although spiritual care interventions have shown psychological benefits, evidence regarding digital spiritual nursing intervention in pediatric settings remains limited.Purpose: To evaluate the effectiveness of smartphone-based spiritual nursing care in reducing anxiety among hospitalized children.Methods: A quasi-experimental nonrandomized controlled pretest-posttest study was conducted in the pediatric inpatient ward of an Islamic hospital in Indonesia. Sixty children agedunder 18 years were recruited and allocated to the smartphone-based application Spiritual Islamic Nursing Care (SINC) group (n=30) or the control group receiving hospital-based murottal therapy (n=30). This study uses consecutive sampling. The intervention was delivered once daily for three consecutive days. Anxiety was measured at baseline and post-intervention using a validated observation sheet. Within-group changes were analyzed using the Wilcoxon signed-rank test, and between-group differences were assessed using the Mann-Whitney U test. Effect sizes were calculated using r statistics.Results: Both groups demonstrated significant reductions in anxiety scores following intervention (p<0,001). The reduction in anxiety was significantly greater in the SINC group compared with control group (p=0,001; r=0,44), indicating a moderate effect size.Conclusion: Smartphone-based spiritual nursing care demonstrated greater effectiveness than standard spiritual therapy in hospitals in reducing anxiety among hospitalized children. Digital spiritual interventions may offer a scalable and culturally responsive approach to integrating spiritual care into pediatric nursing practice.